Epidemiological evaluations of magnitude and the temporal distributions of feedlot heart disease and bovine respiratory disease - Johnson, Blaine Thomas (Kansas State University, 2022)
The objective of this research was to quantify epidemiologic parameters and associations of risk factors of heart disease in feedlot cattle as well as to analyze temporal distributions of first treatment bovine respiratory disease (BRD) in cohorts with high and low morbidity. Three retrospective studies were conducted to evaluate risk and timing of heart disease in feedlot cattle evaluating different sample populations (individual and cohort data). An additional investigation was performed utilizing retrospective data from a different sample population to investigate BRD morbidity magnitude and timing. Individual first treatment records were utilized to determine if cohorts were high (≥ 15% BRD) morbidity or low (<15% BRD) morbidity, then data were analyzed by clustering on the cumulative distribution of timing of first BRD treatments. A risk association analysis was performed on cohort demographics and risk factors for respective clustering groups. Feedlots utilized multiple diagnoses for heart disease, and multiple case definitions of heart disease increase the risk of potential misclassification. Deaths due to heart disease was seven per 10,000 cattle placed at a feedlot. Risk factors for a cohort having at least one heart disease death included sex, average cohort arrival weight, year of placement, length of cohort feeding period up until 325 days on feed, and number of cattle received per cohort. Timing of a heart disease death was found to have a mean and median days on feed of 110 days. Cohort demographics associated with the timing of heart disease were average cohort arrival weight which was modified by placement year. Year of placement was also modified by placement quarter on the timing of heart disease death. Steers were found to die later in the feeding phase compared to heifers. The second investigation utilized individual animal treatment records and cohort data to analyze associations of disease treatment and risk of heart disease in feedlot cattle. This study found that cattle were removed from their respective cohort at a rate of nine per 10,000 cattle placed due to heart disease. Furthermore, cattle died with a heart disease diagnosis at a rate of six per 10,000 cattle placed resulting in a total of 15 heart disease cattle per 10,000 cattle received that did not finish with their respective cohort. The number of BRD treatments was associated with the risk of heart disease and the magnitude of risk was influenced by average cohort arrival weight. Treating cattle for acute interstitial pneumonia (AIP), BRD, and complex disease was associated with increased risk of terminal heart disease diagnosis. Heart disease risk was influenced by feedlot elevation and average cohort arrival weight. The third and final investigation of heart disease reported risk and timing of right heart failure (RHF) when using a specific case definition in feedlot cattle from Canada and the U.S. These data found that cattle breed (beef, dairy, dairy-cross), type (yearling, calves), treatment of BRD (yes/no), cohort BRD morbidity (0 to 5%, 6 to 12%, 12.1 to 27% and >27%), elevation category, sex, arrival quarter and arrival year were associated with risk of RHF. These data also reported that cattle had an unadjusted risk of RHF of 7.8 cattle per 10,000 cattle placed. Timing of RHF death was on average of 179 days on feed and had a median of 174 days on feed unadjusted. The demographic and risk factors used to associate risk with RHF were also found to be associated with timing of RHF and several interactions were evaluated for their influence of timing of RHF. The fourth investigation utilized individual and cohort data from 10 US feedlots. Cohorts were divided into HIGH (≥ 15% BRD) morbidity or LOW (<15% BRD) morbidity based on cumulative first treatment BRD within a cohort. Cohorts were clustered on the cumulative timing of their respective first treatment BRD. Descriptive and statistical analysis were performed on all groups from the cluster analysis as well as the inclusion of cohorts that did not report any treatments for BRD. Results indicated shrink, average cohort arrival weight, ADG, sex, death loss, railed cattle, and number of cattle received were associated with clustering group. In conclusion, the current research reported novel information on feedlot heart disease and descriptions of the temporal patterns of BRD from high and low BRD cohorts as well as data supporting previous findings of the respective diseases. These data reported many different demographic and risk factors with heart disease risk and timing, as well as, associating with specific clustering BRD timing patterns. This information could be useful in future research.
Keywords: Heart disease; Feedlot; Epidemiology; Bovine respiratory disease (BRD)